Hypoxia, Hypoxia-Inducible Factor-1α, and Innate Antileishmanial Immune Responses - Schatz, Valentin; Neubert, Patrick; Rieger, Franz; Jantsch, Jonathan (Frontiers in Immunology, 2018)
Low oxygen environments and accumulation of hypoxia-inducible factors (HIFs) are features of infected and inflamed tissues. Here, we summarize our current knowledge on oxygen levels found in Leishmania-infected tissues and discuss which mechanisms potentially contribute to local tissue oxygenation in leishmanial lesions. Moreover, we review the role of hypoxia and HIF-1 on innate antileishmanial immune responses.